Peningkatan Hasil PembelajaranTematik Terpadu Menggunakan Model Discovery Learning di Sekolah Dasar - Kurnia, Liza; Fahrudin, Farida; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to improve the learning process integratedof students, in thematic learning using the Discovery Learning model in grade IV of elementary school. This research is a Classroom Action Research, which is using qualitative and quantitative approaches. The subjects of this study were teachers and fourth grade students. The results of this study on: a) RPP cycle I in first meeting was 72.2% (Enough) and in the cycle I of the second meeting was 83.33% (Good) while in the cycle IIto 91.6% (Excellent). b) The implementation of the teacher aspects of the cycle I of the first meeting was 75% (Enough), which is increasing in the cycle I of the second meeting was 85.93% (Good) while in the cycle II to 95.31% (Excellent) c) The implementation on students aspects in the cycle I of the first meeting was 71.87% (Enough), and in thecycle I of the second meeting was 84.37% (Good) which is increasing in the cycle II to 92.18% (Excellent).Thus, the use of Discovery Learning model could  improve the result of this study on integrated Thematic Learning.